Yuck, you suck! : poems about animals that sip, slurp, suck - Yolen, Jane; Stemple, Heidi E. Y. (Millbrook Press, 2022)
Provides a picture book with sixteen illustrated poems about various animals that slurp, suck, sip, and stick, including mosquitos, elephants, and stingrays. Includes a list of anatomical body parts animals use to suck and slurp, additional information about the animals highlighted in the book, and a glossary.